Canadian migration destinations of recent immigrants and interprovincial migrants: Similarities, differences and explanations - Mike Shannon (IZA Journal of Migration, 2015)
Canadian Census data for 1981 - 2006 is used to document substantial differences in the destination locations of immigrants and interprovincial migrants. These differences have increased over time as have differences in the characteristics of the two migrant groups. Differences in age, education, and marital status of the two migrant groups explain little of the observed differences. Visible minority status and language differences are somewhat more important; however, much of the difference in migrant group destinations cannot be explained by measured characteristics.
Keywords: 330